c-MET Inhibition Reverses the Osimertinib Resistance in Lung Circulating Tumor Cell Clusters and Suppresses Metastasis - Zhipeng Zhang; Xinyi Lu; Jianhui Tian; Jiaxuan Li; Shihui Liu; Jiajun Liu; Bin Luo; Jialiang Yao; Yao Liu; Yanhong Wang; Wang Yao; Yun Yang; et al. (Biological Procedures Online)
Abstract Background Circulating tumor cells (CTCs) serve as the “seeds” of tumor metastasis, and the clustering of CTCs is critically associated with tumor metastasis and the mortality of lung cancer patients. Inhibiting the survival of CTC clusters represents a pivotal strategy for anti-lung cancer metastasis therapy. This study is designed to explore the impact and underlying mechanism of lung cancer CTC clusters in mediating resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), thereby offering novel insights into anti-lung cancer metastasis treatment. Methods Using the human lung adenocarcinoma CTC line CTC-TJH-01, we performed transcriptome analysis to identify differentially expressed genes. CCK-8, LDH, Calcein AM/EthD-1, and Annexin V-FITC/caspase-3 assays evaluated the effects of osimertinib, Tivantinib, or their combination on CTC-TJH-01 and A549 cell proliferation and apoptosis. RT-qPCR, western blot, and immunohistochemistry analyzed gene and protein expression. A lung metastasis mouse model was established by injecting CTC-TJH-01 clusters, with anatomical observation and H&E staining for evaluation. Results Our study demonstrated that CTC-TJH-01, A549, and H1975 cell clusters in suspension exhibited higher resistance to osimertinib compared to their adherent counterparts. Notably, the expression of the HGF gene was remarkably upregulated in CTC-TJH-01 cell clusters. Activation of the HGF/c-MET pathway was observed in CTC clusters, accompanied by a concurrent downregulation of EGFR protein expression. Significantly, the c-MET inhibitor Tivantinib, but not the HGF inhibitor SRI, effectively suppressed the survival of CTC-TJH-01 and A549 cell clusters. Moreover, Tivantinib, either as a single-agent or in combination with osimertinib, exerted a potent inhibitory effect on the in vivo metastasis of CTC-TJH-01 cell clusters. Conclusion These findings indicate that CTC clusters contribute to resistance against EGFR-TKI treatment, and c-MET inhibitors hold promise as potential therapeutic agents for targeting CTC cluster survival to impede lung cancer metastasis. Graphical Abstract